Preeclampsia frequency and early special metabolic markers of dysadaptation of pregnant women with preeclampsia in the Far North - A. S. Tayurskaya (Acta Biomedica Scientifica)
Preeclampsia is one of the most common obstetric pathologies affecting the level of maternal and perinatal loss. It is manifested through polyorganic dysadaptation state at pregnancy, and depends on the climatic conditions predetermined by fluctuations of temperature and atmospheric pressure. The objective of the work was to identify the frequency of severe preeclampsia in the Far North and the determination of the most sensitive markers of the state of preeclampsia of ulterior degree. Incidence rate of preeclampsia in the Northern areas of Irkutsk region is higher than in its Southern parts. The frequency of severe preeclampsia in these regions did not differ. The most sensitive markers of the state of maladjustment pregnant as a mild form of preeclampsia are the concentration ratios dienes and cortisol.